2010
DOI: 10.1016/j.neuron.2009.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of α-Synuclein Reduces Neurotransmitter Release by Inhibiting Synaptic Vesicle Reclustering after Endocytosis

Abstract: Summary The protein α-synuclein accumulates in the brain of patients with sporadic Parkinson’s disease (PD), and increased gene dosage causes a severe, dominantly inherited form of PD, but we know little about the effects of synuclein that precede degeneration. α-Synuclein localizes to the nerve terminal, but the knockout has little if any effect on synaptic transmission. In contrast, we now find that the modest over-expression of α-synuclein, in the range predicted for gene multiplication and in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
904
6
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 945 publications
(993 citation statements)
references
References 74 publications
(101 reference statements)
69
904
6
14
Order By: Relevance
“…Recent work in Parkinson's disease models with overexpression of wild-type a-synuclein show mainly an inhibitory effect of a-synuclein on neurotransmitter release [29][30][31][32][33][34], whereas two other studies come to the opposite conclusions [35,36]. In one of the latter increased synaptic activity was found in cultured hippocampal neurons acutely injected with a-synuclein.…”
Section: Function Of A-synuclein On Synaptic Activity and Transmittermentioning
confidence: 95%
See 1 more Smart Citation
“…Recent work in Parkinson's disease models with overexpression of wild-type a-synuclein show mainly an inhibitory effect of a-synuclein on neurotransmitter release [29][30][31][32][33][34], whereas two other studies come to the opposite conclusions [35,36]. In one of the latter increased synaptic activity was found in cultured hippocampal neurons acutely injected with a-synuclein.…”
Section: Function Of A-synuclein On Synaptic Activity and Transmittermentioning
confidence: 95%
“…Other effects have also been reported upon a-synuclein overexpression. One study found an increase in synaptic vesicle size, another a decrease of vesicle re-clustering after endocytosis, and two other studies report decreased motility of synaptic vesicles [29,32,46,47]. Interestingly, a-synuclein overexpression has also been shown to increase the amount of vesicles docked to the membranes [31], which would be in line with the recently Abbreviations and symbols: ", increase; #, decrease; À, no change; EM, electron microscopy; EPSC, excitatory postsynaptic current; FCV, fast-scan cyclic voltammetry; fEPSP, field excitatory postsynaptic potential; HPLC, high performance liquid chromatography; mEPSC, miniature EPSC; P, paired-pulse measurements; a-syn, a-synuclein.…”
Section: Function Of A-synuclein On Synaptic Activity and Transmittermentioning
confidence: 99%
“…When suffer from AD, this function is impaired, intracellular calcium ion overload, causing the cells inside and outside calcium ions are relatively close to the static. TME can induce Ca 2+ inflowing, so will also be prompted Ca 2+ outflow rapidly of the Ca 2+ depot, because the stimulation is rhythmic, will cause Ca 2+ concentration of two-way oscillation [37].…”
Section: The Mechanism Of Tme On Ca 2+ Channelmentioning
confidence: 99%
“…This non-linear relationship makes synaptic vesicle fusion to be extremely sensitive changes for Ca 2+ concentration, and which is limited to a very narrow range of Ca 2+ concentration and a very short period. Regeneration of endogenous neurotransmitters including vesicle loading, transshipment and anchoring all need time and process [36,37]. In the process of rapid vesicle exocytosis, vesicles can release to rapid depletion.…”
Section: The Best Target Of Tme Effectmentioning
confidence: 99%
“…Dopamine vesicle function is impaired in patients with PD, suggesting that dysfunctional dopamine handling is fundamental to the disease (14). Genetic mutations in several vesicular-associated proteins, such as α-synuclein, LRRK2 and synaptojanin, can lead to disrupted presynaptic dopamine handling and are commonly linked to PD (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%